“Diálogo entre zorros” - Santistevan De Noriega, Alfonso (2023)
This article analyzes Diálogo entre zorros (Dialogue Among Foxes), a collective creation that represents the origin and history of Villa El Salvador, a community in the southern part of Lima, the capital of Peru, in order to search for the particular characteristics of a collectively created dramaturgy in the historical context of the 1980s. The article reviews the mode of production, creation, and reception of collective creation theatre as a way of responding to traditional theater in order to incorporate new agents, themes, and aesthetics. The analysis of the play allows to discover that, beyond its communicational function, it proposes a dramaturgy rich in dramatic and spectacular resources. Additionally, this research intends to look for connections in this theater experience generated from the community itself, with the concepts and tools of local history and microhistory as well as historiographic practices that collect what the official history does not consider and, from there, generate more general questions. The indiciary paradigm of Carlo Ginzburg and the reduction of scale and microscopic analysis proposed by Giovanni Levi find a methodological and aesthetic correspondence in the practice of the collective creation theater of Diálogo entre zorros.